Current developments in the radiotherapy approach to elderly and frail patients with glioblastoma multiforme. Issue 11 (November 2009) - Roa, Wilson; Xing, James Z; Small, Cormac; Kortmann, Rolf; Miriamanoff, Rene; Okunieff, Paul; Shibamoto, Yuta; Jeremic, Branislav
The benefit of postoperative radiotherapy (RT) has been demonstrated in elderly patients aged 65 years or older with glioblastoma multiforme. Hypofractionated RT schedules can reduce the time and morbidity of treatment while maintaining comparable survival outcomes to lengthy conventional RT. Current international randomized clinical trials are studying the optimized hypofractionated RT regimens, hypofractionated RT in comparison with temozolomide chemotherapy and hypofractionated RT in comparison with the same RT plus temozolomide. Given the guarded prognosis of the elderly and frail patients, quality of life and side effects of treatment should be closely examined. As more than half of cancers in the world occur in developing countries, hypofractionated RT could be better utilized as a cost-effective treatment for this group of patients.